Biscriptal bilingualism differentially affects segmentation of cross-language homophones: Evidence from Hindi and English users. (February 2022) - Vaid, Jyotsna; Chen, Hsin-Chin; Rao, Chaitra
Aims and objectives: Few previous studies of bilingual cognition have theorized the impact of being literate in distinct orthographies. This study examined: (1) How do differences in the way writing systems represent sound affect biscriptal bilinguals' segmentation of spoken words in each language? and (2) What is the impact of the first learned orthography? These questions were addressed in native and non-native readers of Hindi and English. The primary unit of writing in Hindi is the akshara, which corresponds to a syllable in most cases, whereas for English the unit of writing corresponds to a phoneme. Method: Hindi-English users listened to cross-language homophones in Hindi and English. Participants were instructed to take away "the first sound" of each word and say aloud what remained. Data analysis: Percent deletion of the initial phoneme was examined. Exp. 1 included 44 bilinguals. Exp. 2 tested 13 bilinguals. Findings/conclusions: For native English readers the first phoneme was deleted regardless of language. For native readers of Hindi, performance differed by language: the "first sound" was a phoneme for English words but a syllable for Hindi words (except for vowel-initial words). Originality: Using a novel paradigm, this study demonstrates that biscriptal bilinguals' conceptions of speech sounds are differentially shaped by their knowledge of the written forms of those sounds: deleting "the first sound" in /sʌfʌr/ resulted in /fʌr/ when it was presented as a Hindi word but as /ʌfʌr/ when presented as English. Thus, the very same spoken word can yield different conceptions depending on whether it is heard as a word belonging to one language or another. Significance/implications: The findings indicate that language-specific orthographic knowledge influences biscriptal bilinguals' conceptualization of speech sounds in their respective languages. More generally, our study argues for more research on biscriptal bilinguals in the study of bilingual cognition.